Editorial - Vieira, Wilson; Cepêda, Vera Alves; Malta, Maria Mello de (Cadernos do Desenvolvimento, 2024)
Editorial. Cadernos do Desenvolvimento, Centro Celso Furtado, Rio de Janeiro, v. 17, n. 33, set.-dez. 2022.